Pengembangan E-Modul Berbasis Flip Pdf Corporate Materi Momentum Dan Impuls Untuk Siswa Kelas X IPA - Sumarni Sahjat; Suryani Taib; Novira I Lastori (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research was conducted with the following aims: (1). Developing a flip PDF corporate based E-module on momentum and impulse material for class X Science students at Madrasah Aliyah Negeri 2 Tidore Islands. (2). Knowing the feasibility of a flip PDF corporate based E-module on momentum and impulse material. (3). To find out the responses of teachers and students to the corporate PDF flip-based E-module on momentum and impulse material for class X Science students at Madrasah Aliyah Negeri 2 Tidore Islands produced in this research. This development research refers to the 5 steps of ADDIE development design, namely: analysis, design, development, implementation and evaluation. The product trial consisted of validation by material experts, media experts, language experts, physics teachers, and 20 students of Madrasah Aliyah Negeri 2 Tidore Islands class X Science. Data collection used interview guides, expert validation sheets, teacher response sheets and student response sheets. This research produced a product in the form of a flip PDF corporate based E-module and is very suitable for use with eligibility criteria including 87% of media experts which are categorized as very suitable, 86% of material experts which are categorized as very suitable, and 95% of language experts which are categorized as very suitable. The teacher response was 92% in the strongly agree category and the student response was 93% in the strongly agree category.